Beef quality of Nellore steers fed dried or rehydrated and ensiled corn or sorghum grains - Ferreira, Fabiano A.; Chizzotti, Mario L.; Zamudio, Germán D. R.; Estrada, Mauricio M.; Pacheco, Marcos V. C.; Silva, Breno C.; Valadares-Filho, Sebastião C.; Rodrigues, Rafael T. S. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Rehydration of grains, such as corn and sorghum, is used to increase nutrient absorption. However, the effect of this practice on meat quality is poorly understood. Objective: To evaluate the effects of type of grain and processing on the meat quality of Nellore steers in a feedlot. Methods: Twenty-four non-castrated Nellore steers (270 ± 53 kg initial body weight) were distributed in a completely randomized 2×2 factorial design, with six replicates. The first factor was cereal type (corn or sorghum), and the second was the grain processing (dry or rehydrated and ensiled). The diets were composed of 28.44% corn silage and 71.56% concentrate. Sixty days before the beginning of the experiment, corn and sorghum grains were rehydrated and ensiled. The animals were slaughtered after 140 days of confinement. Meat quality analyses were determined in samples of fresh and aged meat (7 days) from the Longissimus lumborum muscle. Results: no difference between treatments was observed for carcass pH and L* (lightness), a* (redness), and b* (yellowness) values, shear force, thawing and cooking losses, and chemical composition of meat (p>0.05). The b* (yellowness) value of subcutaneous fat was higher in steers fed corn, regardless of grain processing (p=0.03). Sarcomere length was higher in aged meat of steers fed sorghum, regardless of processing method (p=0.01). Conclusions: the grain processing method does not affect beef quality; however, grain type can affect subcutaneous fat color and sarcomere length of aged beef.